Dissecting regulated cell death states and transformation mechanisms in the evolutionary trajectory of 30 cancers - Yunpeng Zhang; Qi Ou; Congxue Hu; Chuo Peng; Tengyue Li; Xiaozhi Huang; Kuan Yang; Liyuan Li; Xia Li; Yingqi Xu (iScience)
Summary: Cancer is a heterogeneous disease driven by dysregulated cell death, which influences tumor progression and treatment responses. It is important to construct a systematic landscape that characterizes the dysregulation of regulated cell death (RCD) in tumor cells and accurately depicts the evolutionary relationships between different cell death types within these cells. Using single-cell analysis tools, we analyzed 477,766 tumor cells from 458 samples across 30 cancer types and identified 178 relationships between 15 RCD states and cancers. Pyroptosis and immunogenic cell death were found to be prevalent in most cancer types, especially skin, hematologic, digestive, urological, and lung cancers. We identified 37 significant interaction patterns, 22 transformation modules, and 153 driver genes linked to RCD evolution in 23 cancer types. Additionally, we developed “Secret,” a visual platform for RCD-related research. This study highlights the role of RCD in cancer progression and provides insights for targeted RCD-based therapies.